Study on Performance of Thermoelectric Generator in Living Room Usage - Muhammad Haziq Safiy Zulkiflee; Farah Liana Mohd Redzuan (Journal of Advanced Research Design, 2024)
The rapid development of the present era gives us awareness of harvesting wasted energy using an alternative method besides choosing burning fuels as a primary energy resource. The effort in developing a renewable harvester method has resulted from most of the technologies that are able to be sustained compared to unrenewable resources. The thermoelectric generator (TEG) is one of the technologies that converts heat energy into electrical energy and are continuously studied to ensure our future generation can benefit from it. This device has many advantages compared to the other available energy harvester, which does not need any mechanical component to operate with a small and compact size. With the increasing energy consumption in buildings and houses, finding a way to capture heat energy located in the place was considered. In this study, an analytical procedure was performed by using simulation modelling of MATLAB/Simulink software with the derivation of the equation on TE to find the most feasible way to harvest this heat energy in the living room area by first selecting the TE modules that is available in the market. The TE module showed that the average generation power and the average voltage were 0.03 W and 0.35 V, respectively. It was shown that 16 modules could provide enough power for the internet of things (IoT) devices like those used in sensors and controllers. To conclude, the desirable option to install a TEG block is at the ceiling bottom surface as the ceiling receives more heat than the wall for the tropical climate in Malaysia.